PENERAPAN LEAN MANUFACTURING PADA PROSESPACKING COMPONENT CYLINDER HEAD PT.XYZ DENGANSISTEM DINAMIS - Khairunnissa Nur Fajrin (2020)
As one of the company manufacture that moves in industry vehicles. PT.XYZ having a line of business in by doing export engine. Component The process of a component of the production of, Cylinder Head Inspection, packing, of all the process related, so that when there is a process not go well will impede the process of. their nets Based on observation and questioner seven waste in the process of packing cylinder head was found the waste of unnecessary motion, defects, and transportation with the waste then going to affect productivity work station packing cylinder head. The purpose of this research recommended improvement to the work station packing Cylinder Head and model system packing cylinder head with a method of a Dynamic System so that it obtained the condition of increased productivity. This research was preceded by the use-Value Stream Analysis Tools, the Value Stream Mapping, Causal Loop Diagram, Stock and Flow Diagram, followed by using an application Powersim 10. The results of this research suggest there is a waste of unnecessary motion, defect transportation caused by the work station, layout method of working, and the human factor. Productivity is measured by the simulation shows the results of a pattern productivity work station packing cylinder head has been decreasing, so that in twelve next month productivity show reaching of 98,11 % serve 89,91 %.From the proposals which are given to reduce the total time the initial processes for 422 second to 251 seconds to the inspection process Cylinder Head with a total a reduction of 171 seconds.To a proposal for the act of based on the simulation who performed with raise demand cylinder head be 1,7 % and increase the capacity of the station packing cylinder head be 1,89 % product conditions to achieve it Workstations cylinder head that rises